1998
DOI: 10.1523/jneurosci.18-17-06790.1998
|View full text |Cite
|
Sign up to set email alerts
|

Dendrodendritic Inhibition in the Olfactory Bulb Is Driven by NMDA Receptors

Abstract: At many central excitatory synapses, AMPA receptors relay the electrical signal, whereas activation of NMDA receptors is conditional and serves a modulatory function. We show here quite a different role for NMDA receptors at dendrodendritic synapses between mitral and granule cells in the rat olfactory bulb. In whole-cell patch-clamp recordings in bulb slices, stimulation of mitral cells elicited slowly decaying, GABA A receptor-mediated reciprocal IPSCs that reflected prolonged GABA release from granule cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
377
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(420 citation statements)
references
References 71 publications
40
377
3
Order By: Relevance
“…This is consistent with the electrophysiological results of Schoppa et al (1998), who analyzed miniature EPSCs in granule cells. However, these results leave open the possibility that a small number of dendrodendritic synapses contain NMDA receptors but not AMPA receptors (an even smaller number could be endowed with the complementary receptor profile).…”
Section: Glutamate Receptors In Granule Cellssupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with the electrophysiological results of Schoppa et al (1998), who analyzed miniature EPSCs in granule cells. However, these results leave open the possibility that a small number of dendrodendritic synapses contain NMDA receptors but not AMPA receptors (an even smaller number could be endowed with the complementary receptor profile).…”
Section: Glutamate Receptors In Granule Cellssupporting
confidence: 92%
“…It has been shown that dendrodendritic synapses possess unique functional properties, such as a dependence on NMDA receptors rather than AMPA receptors for their activation (Isaacson and Strowbridge, 1998;Schoppa et al, 1998). Here, we have shown that NMDA and AMPA receptors are colocalized at dendrodendritic synapses and that they are distributed along the entire postsynaptic specialization of granule cell spines.…”
Section: Glutamate Receptors In Granule Cellsmentioning
confidence: 61%
See 2 more Smart Citations
“…Conventional whole-cell recordings with Cs + -internal solution in the pipette were performed in the presence of TTX (1 µM) to block Na + channels and thus prevent any contribution of axonal transmission. A depolarizing voltage step reported to evoke a relatively slow inward Ca 2+ current (Isaacson and Strowbridge 1998;Schoppa et al 1998;Taniguchi and Kaba 2001;Castro et al 2007) was followed by IPSCs (Fig. 5A).…”
Section: Na-enhanced Gc Responses To 10-hz Stimulationmentioning
confidence: 96%